Assessment of Nitrate Reductase Activity in the Leaves of Terminalia chebula - Chaukiyal, S. P.; Mir, Rayees Afzal (Indian Forester, 2010)
Combinations of different concentrations of substrate (0.10M, O.15M, O.20M, and O.25M KNO3) with different pH of buffer (O.20M, KH2P04 of the pH 6.5,7.0, 7.5, 7.6, 7.7, 7.8, 7.9 and 8.0) soiutions were tried for the nitrate reductase activity of Terminalia chebula leaves. Maximum nitrate reductase activity was observed in the combination of buffer solution of O.20M having pH 7.6 and substrate solution 01 the concentration O.15M.